Aphidomorpha (Insecta: Hemiptera) in the entomological collection of the Zoology Research Group, University of Silesia in Katowice (DZUS), Poland - Wieczorek, Karina; Junkiert, Łukasz; Trela, Joanna; Depa, Łukasz; Kanturski, Mariusz; Bugaj-Nawrocka, Agnieszka (Zootaxa, 2022)
The digitisation of the entomology resources of the Department of Zoology, University of Silesia DZUS (presently the Zoology Research Group, Katowice, Poland) allow presenting a substantial collection of aphids, adelgids and phylloxerids (Hemiptera: Aphidomorpha). The collection preserves more than 12 500 curated specimens stored as over 9 500 slides representing 683 taxa (645 identified to the species level and 38 identified only to the genus level), 160 genera, three families and 15 subfamilies. Thirty species represent type material. The geographical analysis of the Aphidomorpha collected shows mainly Eurasian areas, with particularly good representation from Central Europe (especially Poland). The highest diversity is represented by species of Aphididae (98.6%), with the richest in samples subfamily Aphidinae (65.2%). Four hundred twelve genera (972 taxa) of host plants from 99 families were identified among the slide-mounted specimens. A new name—Aphis (Aphis) jaroslavholmani nom. nov. is proposed for Aphis (Aphis) holmani Kanturski & Bezděk, 2019.